Fostering Religious Tolerance in Students through Children's Spirituality (CSE) Education - Alamsyah, Adam; Rahmat, Munawar; Tandigego, Kalvin Rongre; Najib, Muhammad Ainun (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This article aims to explore the Islam-based Children's Spirituality Education (CSE) model in forming students' religious tolerance. This research employs qualitative research incorporating literature study and interviews with numerous teachers teaching religion subject. The research results show that there are four principles of the Islamic CSE model that play a crucial role in strengthening students' religious tolerance, including; 1) respect for other people's beliefs, 2) building a logical, rational and inclusive way of thinking, 3) a spirit of seeking the truth and respecting different truths, and 4) building a spirit of religious moderation and living peacefully side by side with religious beliefs. The advantage of this model lies in its holistic and diverse approach to shaping students' spirituality and recognizing spiritual, emotional, social and cognitive dimensions as an integral part of individual development. The positive implications for Islamic Religious Education include actualizing children's potential according to the principles of Islamic spirituality, supporting the goals of spiritual and moral education, and stimulating understanding of the levels of spirituality in Islam. This model is an effective means of implementing an attitude of tolerance towards non-Muslims through an inclusive and respectful approach towards other beliefs.